Accurate preoperative prediction of non‐organ‐confined bladder urothelial carcinoma at cystectomy. (13th July 2012) - Green, David A.; Rink, Michael; Hansen, Jens; Cha, Eugene K.; Robinson, Brian; Tian, Zhe; Chun, Felix K.; Tagawa, Scott; Karakiewicz, Pierre I.; Fisch, Margit; Scherr, Douglas S.; Shariat, Shahrokh F.
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? Upstaging to non‐organ‐confined (NOC) disease is frequent at the time of radical cystectomy for urothelial carcinoma of the bladder (UCB). Pre‐surgical models that can accurately predict which patients are likely to have more extensive disease are sparse. The present study developed an accurate nomogram for the prediction of NOC‐UCB based on a cohort of patients with clinically organ‐confined disease. Adoption of such a tool into daily clinical decision‐making may lead to more appropriate integration of perioperative chemotherapy, thereby potentially improving survival in patients with UCB. Objective To create an accurate pre‐cystectomy decision‐making tool that allows for the accurate identification of patients with clinically organ‐confined urothelial carcinoma of the bladder (UCB) who have non‐organ‐confined UCB (NOC‐UCB) at cystectomy, as identification of patients with UCB most likely to benefit from neoadjuvant chemotherapy (NACTx) is hampered by inaccurate clinical staging. Patients and Methods A prospectively maintained single‐institution database containing 201 patients who underwent cystectomy and pelvic lymph node (LN) dissection without NACTx for UCB was analysed. Predictive variables for NOC‐UCB included, among others, age, gender, transurethral resection of bladder tumour (TURBT) findings (stage, grade, histology, size, presence of carcinoma in situ, lymphovascular invasion [LVI], multifocality), history of intravesical therapy, time from TURBT to cystectomy, and cross‐sectional imaging findings. Results Clinical stage distribution was 19 patients with Ta, 15 with Tis, 67 with T1, and 100 with T2. At the time of cystectomy, NOC‐UCB and LN‐positive disease were found in 71 (35%) and 38 (19%) of patients, respectively; 81 (40%) of patients had NOC‐UCB (≥pT3/Nany or pTany/N+). Tumour stage (P [trend] <0.001), presence of LVI (odds ratio [OR] 5.2; P = 0.02), and radiographic evidence of NOC‐UCB or hydronephrosis (OR 3.2; P = 0.01) were independently associated with ≥pT3 Nany UCB. Tumour stage (P [trend] < 0.001) and presence of LVI (OR 6.64; P = 0.01) were independently associated with (≥pT3/Nany or pTany/N+) UCB. A nomogram to predict (≥pT3/Nany or pTany/N+) based on all three variables was highly accurate (area under the curve 0.828) and well calibrated, deviating <8% from ideal prediction. Decision curve analysis showed net benefit across all threshold probabilities. Conclusions NOC‐UCB can be predicted with high accuracy by integrating standard clinicopathological factors with imaging information. This model may help to identify patients with NOC‐UCB who may benefit from NACTx.